CANNABIS-DERIVED PHARMACEUTICAL PRODUCTS: THERAPEUTIC, PHARMACOKINETIC AND CLINICAL IMPLICATIONS - A COMPREHENSIVE REVIEW - Ganga Srinivasan; Deepak Shukla
Cannabis, a diverse compounded plant with a rich cultural and scientific history, has garnered significant attention due to its therapeutic and medicinal potential. The plant$1 (Bs main active compounds, phytocannabinoids, notably (SE(B9-tetrahydrocannabinol (THC) and cannabidiol (CBD), play important roles in its effects. Cannabis formulations range from traditional herbal preparations to modern innovations like edibles, sprays, topicals and vaporizable products. Achieving consistent potency, controlled release, and desirable pharmacokinetics remain a challenge. The article delves into its diverse formulations obtained along with its routes of administration. The article provides an overview of cannabinoids-based formulations, highlighting their significance in the context of emerging therapeutic and commercial opportunities, while acknowledging the need for further research to optimize formulations and maximize benefits.s